(untitled) (Oxford, 2000)
A clear guidebook on the implementation of conservation techniques. Uses nineteen case studies to illustrate a range of methods for ecological research, monitoring, planning, education, habitat management and combining conservation with development. These case studies show how these methods are put into action. Softcover
Keywords: Biological diversity conservation